(untitled) (Arghand Journal of Social Sciences, 2025)
Purpose – Many contemporary Pashto novelists depicted realistic pictures of Afghan society. However, Nasir Ahmad Ahmadi has effectively and pragmatically presented a vivid depiction through his literary creations, particularly the novels and stories. Among 25 works, Ahmadi’s novels are well-read by large ‎audiences inside and outside the country. This study critically examines the symbolic representation of animal characters in Akh! ‎Watana (Oh! Homeland) is a novel that highlights how these characters serve as powerful allegories of the social, cultural, and moral realities of Pashtun society. It also analyses animal characters that embody human traits and societal issues, such as corruption, tribalism, ignorance, and ethical decay, rather than merely serving as literary embellishments. ‎ Method – This qualitative study is conducted through literary research that enriches our perception of nature and human life. Various authentic books, BA students’ monographs, literary essays, and online scholarly databases, e.g., Google Scholar, ResearchGate, and others, were also used as data sources. To interpret the data, the literary and thematic analysis techniques were employed to meet the objectives. Results – This study explored the layers of meaning embedded within the symbolic characters, ‎demonstrating how they reflected both individual and collective struggles. The study further ‎contextualised Ahmadi’s narrative within the tradition of allegorical literature, underscoring its ‎significant contribution to contemporary Afghan literary discourse. Practical Implications – Ultimately, the novel’s use of animal characterisation not only critiques prevailing social injustices but also calls for moral awakening and societal reform. It also helps to invite readers to engage in deep self-reflection and heightened social consciousness, not in the original language, such as Pashto, but in English. Originality/Novelty – This research provides a critical analysis of Ahmadi’s novel ‘Akh! Watana not only fills a knowledge gap but also a methodological one, offering new insights and perspectives on Pashtun writers and experts. Keywords – Nasir Ahmad Ahmadi, Akh! Watana Novel, Animal characters, Symbolism